2018
DOI: 10.2196/mhealth.9486
|View full text |Cite
|
Sign up to set email alerts
|

Mobile App Delivery of the EORTC QLQ-C30 Questionnaire to Assess Health-Related Quality of Life in Oncological Patients: Usability Study

Abstract: BackgroundMobile apps are evolving in the medical field. However, ongoing discussions have questioned whether such apps are really valuable and whether patients will accept their use in day-to-day clinical life. Therefore, we initiated a usability study in our department.ObjectiveWe present our results of the first app prototype and patient testing of health-related quality of life (HRQoL) assessment in oncological patients.MethodsWe developed an app prototype for the iOS operating system within eight months i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
3
21
0
Order By: Relevance
“…However, the need for permanent close PRO monitoring is obvious, and in the future, the assessment will be done electronically. In our previous works, we could show that both patients and physicians are willing to participate via app-/web-based tools [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the need for permanent close PRO monitoring is obvious, and in the future, the assessment will be done electronically. In our previous works, we could show that both patients and physicians are willing to participate via app-/web-based tools [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…To date, all clinical results reported include toxicity but not patient-reported outcomes (PRO), which are becoming more and more relevant since modern documentation methods and advanced communication with patients via online tools such as app-based and web-based become available [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding applications targeted at the patient, recently, Kessel et al 3 tested the usability by patients of an application for applying the QLQ-C30 questionnaire of the EORTC to assess health-related quality of life in oncological patients. The study involved 81 patients with a mean age of 55 years and found an average time of 4 minutes to complete the questionnaire on an iPad.…”
Section: Objectivementioning
confidence: 99%
“…Another article also published in 2018 in the form of trial by the same institution of Kessel et al 3 intends to prospectively evaluate the feasibility of using a mobile application to provide systematic support to oncology and radiology patients throughout the future course of their radiotherapy, with the specific objectives to monitor the patients' symptoms and facilitate the exchange of relevant information between patients and physicians. Finally, El Shafie et al 8 intend to research the general performance, quality of life, and need to see a doctor in person of patients undergoing curative Oncologic therapy support via means of a dedicated mobile app (Optimise-1): protocol for a prospective pilot trial…”
Section: Objectivementioning
confidence: 99%
“…With the spread of mobile technology, structured high-quality data (electronic patient-reported outcomes) can be submitted from the patients themselves and become directly integrated into their records [18]. It has been demonstrated that this is feasible in a general population [19][20][21], and the acceptance rates of such solutions both on the patient side and the side of healthcare providers appear high. Electronic patient-reported outcome measures (ePROMS) enable structured first-hand data and open up the possibility to analyse the psychophysiological background of a reported incident as patient-centred IT may soon be able to connect such reports with measurements from miniature, wearable sensors and devices [22].…”
mentioning
confidence: 99%